(untitled) (Baghdad Science Journal, 2014)
This study was conducted to detect the relationship between organic content in the sediment of Rivers Tigris and Diyala, at two locations south of Baghdad, with some environmental factors and the benthic invertebrates and values of diversity indices. Monthly samples collected from the area for the period November 2007 to October 2008. Results showed differences in the physical and chemical characteristics of the two sites, Where the annual average in Tigris and Diyala were respectively for: water temperature (19, 20) C°, pH (8, 8), dissolved oxygen (4, 8) mg / l , Biochemical oxygen Demand BOD5 (3,44 ) mg/l, TDS (632,1585) mg / l, TSS (42, 44) mg / l, turbidity (28,74) NTU, and total hardness as CaCO3 (485,823) mg / l ,Sulfate as SO4 ?(183,366),And finally nitrate as NO3 (4, 6) mg / l. Significant differences were found in the organic matter content as a percentage in the sediments of Diyala River for most months of the study period. Annual average of the percentage of organic matter in the samples of Tigris and Diyala Rivers were respectively: 0.7425 and 1.1375. The benthic groups included variety of benthic organisms; insects, Oligochaetes, Mollusks, and Crustaceans. Highest population density in Tigris River was for insects 31493 individual / m2, Mollusks 23177 individual / m2, Oligochaetes 10774 individual / m2, and Crusteacea 176 individual / m2 which were confined to Tigris River. In Diyala River highest population density was 9908, 18046, 82649 individual / m2 for Mollusks, Insects and Oligochaetes respectively. Values of diversity indices of benthic invertebrates were highest for species richness and equitability in Diyala River respectively, 18.6 and 8.29 in February, while lower values for species richness and equitability in Tigris River were respectively 1.56 and 3.31 in the same month. Most groups of invertebrate have shown significant positive and negative relationships with the physical and chemical and organic characteristics in both Rivers.